Image Compression with a Geometrical Entropy Coder - Guleryuz, O. G.; da Cunha, A. L. (2006 International Conference on Image Processing, 2006)
In this paper we propose a geometrical entropy coder to compress images with geometry. Our proposed scheme works on quantized coefficients of the discrete wavelet transform (DWT). The geometry inherent in those coefficients is exploited by means of directional, predictive coding. We accomplish directional prediction with the aid of the coefficients of the undecimated wavelet transform (UDWT), which are estimated from the available DWT ones both at the encoder and decoder. Following directional prediction, a simple entropy coder takes care of the remaining redundancy. The resulting codec attains competitive performance.